Moral courage in nursing: refining the concept - Pajakoski, Elina (fi=Turun yliopisto|en=University of Turku|, 2025)
ABSTRACT The concept of moral courage in nursing belongs to the field of nursing science. It is linked to nurses’ moral actions, standing up for individual and professional values despite personal risks. In the literature, there is an increase in studies related to moral courage, with the main studies presenting partly varying definitions of moral courage and using self-assessment instruments in hospital settings, with varying constructs and contents. This doctoral study aimed to clarify and refine the concept of moral courage in nursing with the Hybrid Model of Concept Development, comprising theoretical, fieldwork and final analytical phases, including also the evaluation of the maturity of the concept. The theoretical phase comprised an integrative literature review. The fieldwork phase included a survey on nurses’ (n=205) self-assessed level of moral courage and a narrative study on nurses’(n=14) justifications for morally courageous acts and the consequences of the acts. In the analytical phase, a refined concept definition was formed. The maturity of the concept was evaluated in the theoretical and final analytical phases. Moral courage manifests itself in ethical conflicts. Nurses pondered justifications for morally courageous acts and identified the consequences of their acts for themselves, the patients and the work community. Nurses self-assessed their level of moral courage to be moderate or high. Theoretical knowledge combined with versatile examples in empirical data sets enhanced the formation of a clarified, refined definition of the concept. In the final analytical phase, the concept was evaluated as more mature than in the theoretical phase because of the clarified and refined antecedents, attributes and consequences, which were based on rich empirical data cases. The refined concept definition provided in this study strengthens the knowledge base of nursing ethics. The development of the conceptual basis of moral courage gives possibilities for developing processes that support nurses’ morally courageous acts, and that further actions are taken in the organisation to improve the situation. Additionally, the results can be used in theory development concerning the concept. KEYWORDS: Moral courage, ethics, ethical conflict, nursing, concept analysis, concept maturity, hybrid model

TIIVISTELMÄ Käsite moraalinen rohkeus hoitotyössä kuuluu hoitotieteen alaan. Se kytkeytyy hoitotyöntekijän moraaliseen toimintaan, omien ja ammatillisten arvojen puolustamiseen eettisissä ongelmatilanteissa henkilökohtaisista riskeistä huolimatta. Moraalista rohkeutta tarkastelevien tutkimusten määrä on lisääntynyt kirjallisuudessa, ja tutkimuksissa moraalista rohkeutta on määritelty osittain eri tavoin, käyttäen eri rakenteisia ja sisältöisiä itsearviointimittareita sairaalaympäristöissä. Väitöskirjatutkimuksen tarkoituksena oli selkeyttää ja tarkentaa käsitettä moraalinen rohkeus hoitotyössä hybridimallia noudattavalla käsiteanalyysillä, joka koostuu teoreettisesta, empiirisestä ja analyyttisestä vaiheesta, sisältäen käsitteen kypsyyden arvioinnin. Teoreettinen vaihe oli integratiivinen kirjallisuuskatsaus. Empiirisessä vaiheessa toteutettiin kyselytutkimus hoitotyöntekijöiden (n=205) moraalisen rohkeuden itsearvioidusta tasosta ja narratiivinen tutkimus sairaanhoitajien (n=14) perusteluista moraalisesti rohkeille teoille sekä tekojen seurauksista. Analyyttisessä vaiheessa muodostettiin tarkennettu määritelmä käsitteelle. Käsitteen kypsyyttä arvioitiin teoreettisessa ja analyyttisessa vaiheessa. Moraalinen rohkeus ilmenee eettisissä ongelmatilanteissa. Sairaanhoitajat pohtivat perusteluita moraalisesti rohkeille teoille ja tunnistivat tekojensa seurauksia itselleen, potilaalle sekä työyhteisölle. Hoitotyöntekijät arvioivat moraalisen rohkeutensa tason keskitasolle tai korkeaksi. Teoreettinen tieto yhdistettynä monipuolisiin esimerkkeihin empiirisessä vaiheessa mahdollistivat käsitteen selkeyttämisen ja tarkennetun määritelmän muodostamisen. Käsite arviointiin kypsemmäksi kuin teoreettisessa vaiheessa, koska monipuolisiin empiirisiin esimerkkeihin perustuvat ennakkoehdot, ominaisuudet ja seuraukset selkeytyivät ja tarkentuivat. Tässä tutkimuksessa tehty käsitteen tarkennettu määritelmä vahvistaa hoitotyön etiikan tietoperustaa. Moraalisen rohkeuden käsitteellisen perustan vahvistaminen antaa mahdollisuuksia kehittää käytännön hoitotyöhön prosesseja, jotka tukevat hoitotyöntekijöiden moraalisesti rohkeita tekoja ja sitä, että asian kohentamiseksi tehdään organisaatioissa jatkotoimenpiteitä moraalisesti rohkeiden tekojen jälkeen. Tuloksia voi myös hyödyntää käsitteeseen liittyvässä teorianmuodostuksessa. AVAINSANAT: Moraalinen rohkeus, etiikka, eettinen ongelma, hoitotyö, käsiteanalyysi, käsitteen kypsyys, hybridimalli